5G‐assisted telementored surgery. Issue 12 (4th September 2019) - Lacy, A. M; Bravo, R.; Otero‐Piñeiro, A. M.; Pena, R.; De Lacy, F. B.; Menchaca, R.; Balibrea, J. M.
Abstract : Safe and effective implementation of remote surgery and telementoring can have significant limitations. Fifth‐generation (5G) wireless networks could be useful in overcoming these drawbacks. As a proof of concept, the authors present technical and clinical details of two procedures assisted by telementoring using 5G that were also broadcast live. Secure remote access advice